Rapid quality improvement in a preterm birth clinic care pathway during the COVID-19 pandemic. Issue 4 (28th December 2020) - Zarasvand, Sara; Bayar, Erna; Adan, Malko; Mountain, Katherine; Lewis, Holly; Joash, Karen; Teoh, TG; Bennett, Phillip R; Das, Sabrina; Sykes, Lynne
Abstract : Background: Preterm birth (PTB) occurs in 8% of births in the UK. At Imperial College Healthcare NHS Trust, our PTB prevention clinic manages the care of approximately 1000 women/year. Women referred to the clinic are seen from 12 weeks of pregnancy with subsequent appointments every 2–4 weeks to measure cervical length (CL) using transvaginal ultrasound (TVUS). Women with a history of cervical weakness or short cervix on TVUS are offered a cervical cerclage. Local problem: During the COVID-19 outbreak, pregnant women were strongly advised to avoid social mixing and public transport. The National Health Service had to rapidly adopt remote consultation and redesign clinical pathways in order to reduce transmission, exposure and spread among women at high risk of PTB. Methods: We focused on Specific, Measurable, Achievable, Realistic and Timebound aims and used a driver diagram to visualise our changes. We used a series of Plan Do Study Act cycles to evaluate and adapt change ideas through the UK's national lockdown during the COVID-19 pandemic between 23 March and 29 May 2020. Results: We reduced the number of face-to-face appointments by 54%. This was achieved by increasing remote telephone consultations from 0% to 64%, and by reducing the intensity of surveillance. The rate of regional anaesthetic was increased from 53% to 95% for cerclage placement in order to minimise the number of aerosol-generating procedures. Patient and staff satisfaction responses to these changes were used to tailor practices. No women tested positive for COVID-19 during the study period. Conclusions: By using quality improvement methodology, we were able to safely and rapidly implement a new care pathway for women at high risk of PTB which was acceptable to patients and staff, and effective in reducing exposure of COVID-19.